Pengaruh Pasir Pulau Bungin Kabupaten Kuantan Singingi Pada Campuran Laston Lapis Fondasi/Asphalt Concrete Base (AC-BASE) - Arief Rahman; Sri Djuniati; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Sand of Pulau Bungin is a natural sand that comes from Batang Kuantan River, Kuantan Singingi Regency. The existence of sand of Pulau Bungin makes development progress in Kuantan Singingi Regency because easily obtained, and more economical no need to bring sand material from other area and not have to go through stone breaking process by stone crusher. Based on the Bina Marga Specification 2010 Revision 3, the use of natural sand for asphalt concrete mixture (AC) should not exceed 15% of the total aggregate mixture weight. Therefore, we need to know the efficiency of using natural sand in concrete asphalt mixture (AC) for optimal utilization. This research aims to find out the optimum asphalt (KAO) and to know Marshall's characteristics whether to meet the Bina Marga Specification 2010 Revision 3. The natural fine aggregate variation of sand used in this research is 0%, 5%, 10%, 15% and 16 % of the total weight of the aggregate mixture. The addition of natural sand in the asphalt concrete mixture of the asphalt concrete base (AC-Base) causes the value of optimum asphalt (KAO) to decrease. On the mixture asphalt concrete base (AC-Base), 5% of the sand content of the 5% content of the optimum asphalt content (KAO) was increased by 6,20% and the largest stability was 3341 kg. Without considering the limits of natural sand usage as set out in the Bina Marga Specification 2010 Revision 3 then the addition of natural sand is still possible in the asphalt concrete base (AC-Base) until 16%.Keywords: Natural sand, asphalt concrete base (AC-Base), a general Specification Bina Marga 2010 Revision 3 and characteristics of Marshall.